2001
DOI: 10.1128/jcm.39.4.1536-1539.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristic-Based Epidemiology of Hepatitis B, C, and E Viruses and GB Virus C/Hepatitis G Virus in Myanmar

Abstract: We carried out a molecular characteristic-based epidemiological survey of various hepatitis viruses, including hepatitis B virus (HBV), hepatitis C virus (HCV), hepatitis E virus (HEV), and GB virus C (GBV-C)/hepatitis G virus (HGV), in Myanmar. The study population of 403 subjects consisted of 213 healthy individuals residing in the city of Yangon, Myanmar, and the surrounding suburbs and 190 liver disease patients (155 virus-related liver disease patients and 35 nonviral disease patients). The infection rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 24 publications
(20 reference statements)
3
39
9
Order By: Relevance
“…Based on the results of this study, the trend of HCV infection could be extrapolated to the general population. Even though the HCV infection rate was lower than expected [10,11] , the predominance of genotype 3 (3a; 26.7% and 3b; 33.5%) of Myanmar immigrant workers in this survey was similar to previous studies [11,12] . HCV-3 is also the predominant genotype in Thailand followed by genotype 1b and genotype 6 ( fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Based on the results of this study, the trend of HCV infection could be extrapolated to the general population. Even though the HCV infection rate was lower than expected [10,11] , the predominance of genotype 3 (3a; 26.7% and 3b; 33.5%) of Myanmar immigrant workers in this survey was similar to previous studies [11,12] . HCV-3 is also the predominant genotype in Thailand followed by genotype 1b and genotype 6 ( fig.…”
Section: Discussionsupporting
confidence: 76%
“…In Myanmar, the first study conducted showed a high prevalence of HCV in thalassemia and liver disease patients [9] . Prevalence varies from approximately 2 to 11.6%, though most studies were performed based on a small sample size [10][11][12] . This variation may result from differences in geographical sampling area and target population.…”
mentioning
confidence: 99%
“…HBV genotypes also have a characteristic geographic distribution (2,15,18,22,24,26). For example, genotypes A and D are predominant in western countries while genotypes B and C are prevalent in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Another classification system, which is based on the sequence diversity of the HBV genome has been developed and, currently eight genotypes designated A to H have been identified (1,4,23,25,35). It has been reported that distribution of HBV subtypes and genotypes varies with different geographical areas (2,15,18,22,24,26). Also, clinical manifestations and therapeutic responses to antiviral therapy might differ with different HBV genotypes (11,12,39 Abstract: Four subtypes (adw, adr, ayw, and ayr) and eight genotypes (A to H) of the hepatitis B virus (HBV) have been identified.…”
mentioning
confidence: 99%
“…GBV-C is particularly notable in that it establishes a persistent, asymptomatic infection within hosts and is widely distributed in the healthy human population. The prevalence of GBV-C ranges between 1% and 14% in healthy blood donors (Moaven et al 1996;Nakai et al 2001;Abe 2001). GBV-C has also been isolated from chimpanzees (Adams et al 1998;Birkenmeyer et al 1998), and the related GBV-A and -B viruses from New World monkeys (Simons et al 1995;Bukh and Apgar 1997).…”
Section: Introductionmentioning
confidence: 99%